MENURUNKAN KECEMASAN MENGHADAPI PRAKTIK BELAJAR KERJA PENYANDANG DISABILITAS FISIK DENGAN BIMBINGAN KELOMPOK - Astri Fajar Atikasari; Vera Imanti (al-Balagh : Jurnal Dakwah dan Komunikasi, 2019)
Every human is born in different conditions. Some of them are born normal, and some are born with physical limitations. In its growth, even normal human conditions can turn into persons with physical disabilities due to several factors. This study aims to determine the effect of group guidance on anxiety in the face of learning practices of persons with physical disabilities. The sample in this study were seven physical disabilities persons who are chosen by using purposive sampling technique. The approach used was pre-experiment with one-group pretest-posttest design. Measurements are made with instruments that measure anxiety facing work learning practices. The measuring instrument consists of 35 items of valid statements and has a reliability coefficient of 0.828. Hypothesis testing shows the results of the Z analysis is -2,366 with Asymp. Sig. 0,018 (p <0,05). It was concluded that Ho was rejected and Ha was accepted, which meant that group guidance could reduce the anxiety of learning practices of persons with physical disabilities.